The relationship between sexual performance and feelings of loneliness with the mediating role of marital boredom - Nezamolmolki, Mitra; Nasri, Maryam; Bahrainian, Seyed Abdulmajid; Shahbazizadeh, Fatemeh; Farahmandpour, Sahar (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This research was conducted with the aim of investigating the relationship between sexual performance and loneliness with the mediating role of marital boredom. Methods: The research method was correlation type. The statistical population of the present study was all married women with family differences who referred to counseling centers in Tehran in 2022. The sample of the research was 200 of these married women, which was done in the form of two-stage cluster and simple random sampling of the lottery type. The research tools were: Pines Marital Boredom Scale (1996), Social Emotional Loneliness Questionnaire of DiTomaso et al. (2004) and Rosen et al. Sexual Performance Questionnaire (2000). The obtained information was analyzed using the method of path analysis and path analysis. Results: Path analysis results showed that there is a direct and significant relationship between sexual performance and marital boredom, between loneliness and marital boredom, and between sexual performance and loneliness (P<0.001). Also, the results indicated that marital boredom plays a mediating role in the relationship between sexual performance and loneliness (P<0.001). Conclusion: It can be concluded that the model of the relationship between sexual performance and loneliness with the mediator role of marital boredom has a good fit.